Topical Mastic Oil for Treatment of Functional Dyspepsia: A Randomized , Triple-Blind Controlled Trial: - Baradaran Sattarzadeh, Mahsa; Shojaii, Asie; Nassiri Toosi, Mohssen; Abdollahi-Fard, Mehri; Alborzi Avanaki, Foroogh; Taher, Mohammad; Shiehmorteza, Maryam; Hashem-Dabaghian, Fataneh (Galen Medical Journal, 2021)
Background: The main goal of the present study was to evaluate the effect of topical mastic oil, compared to placebo on treatment of functional dyspepsia (FD). Materials and Methods: Sixty-three patients with FD were included. Thirty-two subjects received the topical mastic oil (10 drops/TDS after meal) with massage and 31 patients received topical sesame oil with massage. Both groups received pantoprazole (40 mg daily) along with oil and massage. The severity of early satiation, postprandial fullness, epigastric pain and epigastric burning was assessed after 4 weeks using the Visual Analogue Scale (VAS) as well as frequency of symptoms. Satisfaction with the treatment was also assessed using a researcher-made questionnaire. Changes in the severity of symptoms were evaluated by Friedman’s test. Results: Mean and standard deviation of age of the subjects were equal to 36.95±13.64 and 50 (79.4%) patients were female. Both groups experienced a significant decrease in the severity of all the four symptoms (P<0.001). The percentage of decrease in the severity of early satiation was significantly higher in the mastic group than the control group (76.03±34.91% vs. 37.24±38.86%, P=0.003). No significant differences were found in the percentage of decrease in the severity of postprandial fullness, epigastric pain and burning between the study groups (P=0.05, 0.06, and 0.13, respectively). The frequency of symptoms was decreased similarly in both groups. Satisfaction with the treatment was reported to be significantly higher in the mastic group than the sesame group (P=0.01). There were no intolerable side effects in both groups. Conclusion: Mastic oil reduced early satiation better than the placebo. In addition, satisfaction with the treatment was higher in the mastic group than the sesame group. [GMJ.2021;10:e1965]